In-between border spaces in the Levant - Meier, Daniel 1970- (Routledge, Taylor & Francis Group, 2021)
This book focuses on interstitial spaces or in- between borders in the Middle East. Using various case studies, it raises the question how actors living in these regions perform their belonging despite the apparent constraints of history and politics. In recent years, the Middle East has seen States attempts to shape buffer zones or safe zones in border regions, for example, in Syria’s borderlands in the aftermath of the civil war. Typically studies on in- between borders refer to three interrelated aspects: space (territorial, symbolic), power (states or non-state actors) and identity (definition of the self/other). In this volume, the authors investigate these axes of research through the notions of sovereignty and belonging in order to assess how these concepts may highlight in-betweenness through a political dimension. Stemming from a perception of the borders as processes, these various studies aim to explore the theoretical potential of in- between border spaces to re-think sovereignty and identity belonging in such interstitial zones. While notions such as heterotopia, margins, liminality, borderlands, buffer zones, no man’s land or frontiers will be explored, each case study highlights how actors, territory and powers relate to each other in order to improve our understanding of historical and political process that are shaping identities under spatial constraints.
The chapters in this book were originally published as a special issue of the journal "Mediterranean politics", volume 25 (2020), issue 3
Keywords: Buffer states / Middle East; Middle East / Boundaries; Middle East / Social conditions; Middle East / Politics and government; Boundaries; Buffer states; Politics and government; Social conditions; Middle East